Strategic agility, openness and performance: a mixed method comparative analysis of firms operating in developed and emerging markets - Vrontis, Demetris; Belas, Jaroslav; Thrassou, Alkis; Santoro, Gabriele; Christofi, Michael (My University, 2023)
This research delineates the relationship between strategic agility and performance, and proposes openness as a requisite means to fostering agility and enhancing performance. Methodologically, the research follows the pragmatist paradigm through a mixed-method research design, incorporating three separate studies. These comprise a CEO-based survey on foreign firms operating in emerging markets, a CEO-based survey on firms operating in developed countries, and CEO interviews, all of which are complimented by auxiliary instruments of secondary data and an expert panel. The research finds that strategic agility is vital for firms’ performance in both developed and developing markets. Moreover, we found that while search depth amplifies the above relationship in both contexts, search breadth does it only in the context of foreign firms operating in emerging markets. The value of these findings stems from their elucidation of the role of strategic agility in emerging markets and its comparison to that of firms operating in developed countries; their insights into strategic agility’s relationship with openness; their schematic culmination into a systemically and contextually depicted framework; and their prescriptive managerial implications.
Keywords: Emerging markets; External knowledge sourcing; Open innovation; Openness; Performance; Strategic agility